PENGEMBANGAN PRODUKTIVITAS MASYARAKAT PEDESAAN MELALUI PENDIDIKAN LIFE SKILLS BERBASIS SUMBER DAYA LOKAL (Studi Kasus Di Desa Tamantirto Kasihan Bantul) - Aiman, Umul; Sriwijaya, Bambang; Swasono, F. Didiet Heru (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
Tamantirto Village is a village with a population of 728 categories of poor households (28.46%). To reduce the level of poverty which is done by providing knowledge and skills of local resource utilization in the community. Transfer of knowledge and technology conducted by extension, practice, creation of demonstration plots as well as comparative studies. Knowledge and presence will include fish farming, household waste management, recognition and processing of medicinal plants into instant beverage and syrups. The result is a rural communities of Tamantirto was service capable of freshwater fish culture technologies and conduct intensive cultivation with a pool  tarp.  Capable  of  processing  organic  waste  into  compost  and  liquid fertilizer and manage of inorganic waste. Rural communities recognize a variety of  medicinal  plants  in  the  environment  and  can  process  them  into  instant beverages  and  syrups.  Society  has  increased  the  quality  of  life  of  its environmental cleanliness and income